Supplier search and re-matching in global sourcing: Theory and evidence from China - Fabrice Defever; Christian Fischer; Jens Suedekum (Heinrich Heine University Düsseldorf, Düsseldorf Institute for Competition Economics (DICE), 2017)
In this paper, we consider a dynamic search-and-matching problem of a firm with its intermediate input supplier. In our model, a headquarter currently matched with a supplier, has an interest to find and collaborate with a more efficient partner. However, supplier switching through search and re-matching is costly. Given this trade-off between the fixed costs and the expected gains from continued search, the process will stop whenever the headquarter has found a sufficiently efficient supplier. Using firm-product-level data of fresh Chinese exporters to the United States, we obtain empirical evidence in line with the predictions of our theory. In particular, we find that the share of short-term collaborations is higher in industries with more supplier-cost dispersion, an indication of higher expected search opportunities.
Keywords: F23; D23; L23; 330; input sourcing; relational contracts; supplier search